Glucocerebroside inhibits NADPH oxidase activation in cell-free system - Moskwa, Patryk; Palicz, Anita; Paclet, Marie-Hélène; Dagher, Marie-Claire; Erdős, Melinda; Maródi, László; Ligeti, Erzsébet (Biochimica et biophysica acta, 2004)
We reported earlier that monocytes and macrophages from patients with type I Gaucher disease have a decreased capacity to generate superoxide anion (O2−) on stimulation with opsonized S. aureus or formyl-methionyl-leucyl-phenylalanine. In this study, various forms of the cell-free assay system were used to probe the hypothesis that glucocerebroside (GC) accumulating in Gaucher patients' phagocytes may interfere with the activation of NADPH oxidase. Xanthine/xanthine oxidase assay was applied to explore the possibility that GC may scavenge O2−. We found that addition of GC to the crude, semirecombinant or fully purified cell-free systems inhibited activation of NADPH oxidase in a concentration-dependent manner. The inhibitory effect of GC could be overcome by increased concentrations of p47phox and p67phox. In contrast, O2− generation was not decreased by GC added to the assembled, catalytically active enzyme complex. In the xanthine/xanthine oxidase system, GC had no effect on the generation of O2−. These data indicate that assembly of the respiratory burst oxidase of phagocytic cells may be a possible target of the pathologic actions of GC.